CITRA EKSOTIK DALAM NOVEL RONGGENG DUKUH PARUK - Abu Bakar Ramadhan Muhamad (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2018)
Imaging of a discourse in the paradigm of postcolonialism is closely related to the issue of domination and subordination in terms of reference to imperialism or capitalization. The imagery is a project that develops special perceptions about "foreign" (East) regions. This project presupposes that the "foreign" (East) region is exotic "uncivilized" regions, standardized in a special "understanding", whose main purpose is to separate or dissolve it ("tame" the "foreign" region), so that different from or being "civilized". One area that is strongly embedded in this project is literature, with the novel as an aesthetic object. In connection with this issue, this article reveals how the East is presented in its exotic image, so how the image represents an ambivalent relationship between the East (colonized) and the West (invaders), especially in the Ronggeng Dukuh Paruk (RDP) novel by Ahamad Tohari.The results of the study show that the RDP novel is an urgent medium related to the conditions of postcoloniality. The postcoloniality is meant not only that the narrative that is displayed is the essence of what is obtained from the author about the exotic world region (the nature of Paruk dukuh) with all the signs attached to it, narration is also used as an affirmation of identity and historical existence, in the context of civilized culture. The culture in question is the source of identity that is championed as a filter and lifter, for the community that has been known and thought about, as an invitation for emancipation. Power and ability to tell stories, in this case, are used as weapons of the author in hopes of inspiring readers. The expected result is the hegemonic reader of the discourse displayed in the work of the author.In the post-colonial context, this method is inseparable from a combination where political and ideological power is interrelated, where the image represented is always still signifying the "emancipation" power relationship between the West and the East. However, like ideology, imaging must be realized other than as originating from and relating to material conditions and material effects, it is also a misrepresentation of reality and in its rearrangement process. Therefore, the potential, possibilities, and certain visions that follow, are full of content, values, or strategies for "mastering" (power). Especially in the Ronggeng Dukuh Paruk novel by Ahamad Tohari, exotic images give rise to ambivalent meanings for emancipation efforts (West to East).